The measurement of financial performance of government linked companies (GLCS) using dupont analysis / Masriana Abdul Rasyid - Abdul Rasyid, Masriana (2017)
This study aims to investigate whether the DuPont analysis relevant to be used to calculate the profitability in Government Linked Companies (GLCs). This research is to examine the relationship between Financial Leverage (FL), Net Profit Margin (NPM), Total Asset Turnover (TATO), Return on Asset (ROA) and Return on Equity (ROE). The dependent variable for this research is Return on Asset while the independent variables are Financial Leverage, Net Profit Margin, Asset Turnover, Return on Asset. The sources of secondary data were gathered from Osiris will be used as a part of this project. Main data for this research are the annual financial reports on ten companies in the Government Linked Companies industry in 2005 to 2015. Besides that, this research focuses on the 30 Government Linked Companies in Malaysia. In this research used descriptive analysis, regression, normality test and heteroscedasticity.Overall, the relationship between Financial Leverage, Net Profit Margin, Total Asset Turnover and Return on Asset are positive relationship and positive significant with Return on Equity using Regression Analysis. However, by using Correlation analysis there is negative relationship and not significant between Total Asset Turnover with Return on Equity.